Cr3+-Doped double perovskite antimonates: efficient and tunable phosphors from NIR-I to NIR-II. Issue 18 (25th July 2022) - Zhao, Meng; Liu, Shengqiang; Cai, Hao; Zhao, Fangyi; Song, Zhen; Liu, Quanlin
Abstract : By tuning cationic compositions, Cr 3+ -doped antimonate double perovskites present emissions from NIR-I to NIR-II regions. In particular, Ca2 ScSbO6 :Cr 3+ and Sr2 InSbO6 :Cr 3+ feature long-wavelength emissions with high luminescence efficiency. Abstract : Near-infrared (NIR) light devices have great potential in non-destructive testing and biomedicine fields. However, the lack of stable and efficient long wavelength NIR phosphors hinders their development. In this work, utilizing the compositional flexibility of antimonate double perovskites, we realized efficient and tunable broadband NIR emissions based on A2 MSbO6 :Cr 3+ materials (A = Ca, Sr, and Ba; M = Ga, In, Sc, and Y). The NIR emission peaks ranged from 825 to 1010 nm by a composition modulation. In particular, Ca2 ScSbO6 :Cr 3+ exhibits an 850 nm-centering broadband NIR emission with an internal quantum efficiency of 84.5% and a high thermal quenching temperature, retaining ∼71% at 410 K of the initial intensity at 80 K. Comparatively, Sr2 InSbO6 :Cr 3+ with a 920 nm-centering broadband emission has 63.2% internal quantum efficiency. This work could help in discovering novel NIR phosphors with long-wavelength emissions and high efficiency.